2015
DOI: 10.1149/2.0501514jes
|View full text |Cite
|
Sign up to set email alerts
|

Correcting the Hydrogen Diffusion Limitation in Rotating Disk Electrode Measurements of Hydrogen Evolution Reaction Kinetics

Abstract: Rotating disk electrode (RDE) method is widely employed in studies on the hydrogen oxidation/evolution reaction (HOR/HER) owing to its well-defined mass transport behaviors. While it is accepted that the measured HOR current is controlled by both the electrode kinetics and the diffusion of H 2 , HER is typically assumed to be free of diffusion limitation. Here we demonstrate that HER could also be diffusion limited when the electrode kinetics is fast, as evidenced by the rotation speed dependent HER current on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(173 citation statements)
references
References 32 publications
7
165
0
1
Order By: Relevance
“…The HER performance of Pt is also listed in Table 2 for comparison. Note that due to the ultrafast HOR/HER kinetics of Pt in acid, the overpotential at 10 mA cm −2 only comes from mass transport (Equation (4)) and is not related to the kinetics of the catalyst [36].…”
Section: Pgm-free Her Catalysts Active In Acidmentioning
confidence: 99%
“…The HER performance of Pt is also listed in Table 2 for comparison. Note that due to the ultrafast HOR/HER kinetics of Pt in acid, the overpotential at 10 mA cm −2 only comes from mass transport (Equation (4)) and is not related to the kinetics of the catalyst [36].…”
Section: Pgm-free Her Catalysts Active In Acidmentioning
confidence: 99%
“…8 Sun et al reported increased activity with increased particle size for HOR/HER on 2-7 nm Pt nanoparticles in acid, 18 and Ohyama et al reported the same trend for HOR/HER on 2-4 nm Pt nanoparticles in base. 19 However, the rotating disk electrode (RDE) method cannot be used to measure HOR/HER activity on Pt in acid due to the overlapping polarization and concentration overpotential curves, 8,20 and thus the results from Sun et al 18 via RDE measurements might not be reliable. Using the H 2 -pump method in a proton exchange membrane fuel cell configuration, Durst et al characterized the exchange current densities of HOR/HER on 2-9 nm Pt/C and reported no particle size effect.…”
mentioning
confidence: 99%
“…This value is larger than that reported for NiMo/Ni‐foam (30 mV) in the phosphate buffer without the redox ions, which is a standard solution for water splitting in near‐neutral pH conditions . The HER on Pt is known to be kinetically facile, and the observed overpotential is mainly due to the concentration overpotential from the proton donors and hydrogen products . The concentration overpotential is highly dependent on the viscosity of the electrolyte, which alters the diffusion coefficient according to the Stokes–Einstein equation.…”
Section: Resultsmentioning
confidence: 70%
“…[45] The HER on Pt is known to be kinetically facile, and the observed overpotential is mainly due to the concentration overpotential from the proton donors and hydrogen products. [45][46][47] The concentration overpotential is highly dependent on the viscosity of the electrolyte, which alters the diffusion coefficient according to the Stokes-Einstein equation. The diffusion coefficient decreases in viscous solutions, which makes the mass-transport of the reactants and products difficult and results in the increase in concentration overpotential.…”
Section: Evaluation Of Individual Electrochemical Cell Performancementioning
confidence: 99%